Climate adjusted projections of the distribution and frequency of poor air quality days for the contiguous United States - Wilson, Bradley; Pope, Mariah; Melecio-Vazquez, David; Hsieh, Ho; Alfaro, Maximilian; Shu, Evelyn; Porter, Jeremy; Kearns, Edward J. (Frontiers in Earth Science, 2024)
Unhealthy air quality conditions can strongly affect long-term human health and well-being, yet many air quality data products focus on near real-time alerts or short-term forecasts. Understanding the full state of air quality also requires examining the longer term frequency and intensity of poor air quality at ground level, and how it might change over time. We present a new modeling framework to compute climate-adjusted estimates of air quality hazards for the contiguous United States (CONUS) at 10 kilometer horizontal resolution. The framework blends results from statistical, machine-learning, and climate-chemistry models -including a bias-adjusted version of the EPA Community Multiscale Air Quality Model (CMAQ) time series described in (Wilson et al., 2022) for ground-level ozone, anthropogenic fine particulate matter (PM2.5), and wildfire smoke PM2.5 into consistent estimates of days exceeding the 'unhealthy for sensitive groups' (orange colored) classification on the EPA Air Quality Index for 2023 and 2053. We find that joint PM2.5 and ozone orange+ days range from 1 day to 41 days across CONUS, with a median value of 2 days, across all years. Considering all properties across CONUS, we find that 63.5% percent are exposed to at least one orange or greater day in 2023, growing to 72.1% in 2053. For a 7-day threshold, 3.8% and 5.7% of properties are exposed in 2023 and 2053, respectively. Our results also support the identification of which parts of the country are most likely to be impacted by additional climate-related air quality risks. With growing evidence that even low levels of air pollution are harmful, these results are an important step forward in empowering individuals to understand their air quality risks both now and into the future. U.S. Environmental Protection Agency (EPA) leading the design and implementation of policies and standards for regulating air quality levels. Since the implementation of the Clean Air Act, the combined emissions of criteria pollutants and their precursors have dropped by 78% (US EPA, 2016). However, climate change threatens to reduce these gains by altering meteorology in ways that are either directly conducive to pollutant formation or indirectly conducive through secondary factors like wildfires (